Effects of rosiglitazone/PHBV drug delivery system on postoperative fibrosis in rabbit glaucoma filtration surgery model. (1st January 2019) - Zhang, Feng; Liu, Ke; Pan, Zheng; Cao, Mengdan; Zhou, Dengming; Liu, Hairong; Huang, Yuting; Duan, Xuanchu
Abstract: The aim of this study is to investigate the effects and toxicities of poly(3-hydroxybutyric acid- co -3-hydroxyvaleric acid) (PHBV)-loading rosiglitazone on preventing scar formation after glaucoma filtration surgery (GFS) in the rabbit model. Rosiglitazone/PHBV drug delivery system was prepared via electrospinning. Release behavior of RSG/PHBV membrane was evaluated by high-performance liquid chromatography. The different concentration membranes were implanted under the conjunctiva of the rabbit's eyes (RSG/PHBV groups). Also, MMC-soaked sponges were placed under the conjunctiva of the eyes (positive group) for 3 min. Intraocular pressures and bleb features were then assessed for 4 weeks postoperative. Bleb sections were stained with HE, Masson's trichrome and α smooth muscle action (αSMA) immunohistochemistry. The protein expression of collagen I, αSMA, and connective tissue growth factor in the bleb area were then quantified. The following results were observed: (1) the concentration of rosiglitazone would not affect the morphology of RSG/PHBV membrane. (2) RSG/PHBV membrane would effective and safety prevent the formation of fibrosis after GFS in the rabbit model. Implantation of RSG/PHBV membrane prevents scar formation after GFS. What's more, it ameliorated toxicity to conjunctiva and cornea compared with the placement of MMC. The RSG/PHBV membrane would be a more effectivity and safer strategy than MMC.